Targeting the Intracellular Environment in Cystic Fibrosis: Restoring Autophagy as a Novel Strategy to Circumvent the CFTR Defect - Villella, Valeria R.; Esposito, Speranza; Bruscia, Emanuela; Maiuri, Maria Chiara; Raia, Valeria; Kroemer, Guido; Maiuri, Luigi (Frontiers in Pharmacology, 2013)
Cystic fibrosis (CF) patients harboring the most common deletion mutation of the cystic fibrosis transmembrane conductance regulator (CFTR), F508del, are poor responders to potentiators of CFTR channel activity which can be used to treat a small subset of CF patients who genetically carry plasma membrane-resident CFTR mutants. The misfolded F508del-CFTR protein is unstable in the plasma membrane even if rescued by pharmacological agents that prevent its intracellular retention and degradation. CF is a conformational disease in which defective CFTR induces an impressive derangement of general proteostasis resulting from disabled autophagy. In this review, we discuss how rescuing Beclin 1 (BECN1), a major player of autophagosome formation, either by means of direct gene transfer or indirectly by administration of proteostasis regulators, could stabilize F508del-CFTR at the plasma membrane. We focus on the relationship between the improvement of peripheral proteostasis and CFTR plasma membrane stability in F508del-CFTR homozygous bronchial epithelia or mouse lungs. Moreover, this article reviews recent preclinical evidence indicating that targeting the intracellular environment surrounding the misfolded mutant CFTR instead of protein itself could constitute an attractive therapeutic option to sensitize patients carrying the F508del-CFTR mutation to the beneficial action of CFTR potentiators on lung inflammation.